DWELLING AND LIVING CONDITIONS OF THE STUDENTS OF ST. VOLODYMYR UNIVERSITY (1834-1863) (City: History, Culture, Society, 2018)
The article highlights the features of the living conditions of St. Vladimir University students during 1834-1863 years. The types of the housing of two main groups of students (who were educated and maintained by the state and from charitable givings and students who studied at their own expense) are analyzed in the article.A lot of attention was paid to the living conditions of students who were educated from state budget money. The location of the houses and estates in which they lived was defined in the article. It also was found that the living conditions of students who were educated and maintained by the state had a proper level of housing and were generally comfortable for them to live. At the same time, these types of dormitories for poor students were specially designed as a form of control with strict regulation of their everyday life. The habitats of students who were educated and maintained by the state were comfortable for students living and had a proper level of living conditions in general. At the same time, these habitats served as a form of control over university students. The habitats of students who studied at their own expense were significantly different in terms of living conditions. They usually rented accommodation from Kyiv burghers. Typically students rented one room for a few of them because it was cheaper.The poorest students of the university lived in uninhabited rooms (basements, attics). Often, poor living conditions caused a negative impact on students' health and learning progress. Students usually settled near university buildings and formed a compact quarter, mostly inhabited by university students. At the initial stage of the university existence (1834-1842), the students' dwellings were mainly located at Lypky and Pechersk, near the university's leased buildings. During the next period (1842-1863), students mostly settled not far from the main building of the university (red building) or near other buildings of the university, for example, near the anatomical theatre or the military hospital.The features of living conditions of students (heating, lighting, water supply, sanitary and hygienic conditions) are also described in the publication. These factors were very important in shaping student everyday life and influenced the creation of a special students’ lifestyle.
Keywords: students; University of st. Volodymyr; habitation; living conditions